E-042 Immediate procedural outcomes in 35 consecutive pipeline embolization cases: a single-center, single-user experience. (4th July 2012) - Colby, G; Lin, L; Gomez, J; Paul, A; Huang, J; Tamargo, R; Coon, A
Abstract : Background and Objective: Flow diverters are an exciting new class of endovascular devices that treat aneurysms by curative reconstruction of the parent artery. The Pipeline embolization device (PED; Covidien Vascular Therapies, Mansfield, Massachusets, USA) is the first FDA-approved intracranial flow diverting device available in the USA. We present our periprocedural results in a series of 35 consecutive PED cases. Methods: All patients who underwent PED treatment of an intracranial aneurysm at our institution following FDA approval of the device in April 2011 were included in the series. Patient demographics, aneurysm characteristics, procedural details, and technical and clinical outcomes were analyzed. Results: Thirty-four patients (range 23–78 years, mean age 56.4 years) with 41 unruptured aneurysms (37 anterior circulation, 4 posterior circulation, mean size 11.4 mm, 20/21 large or giant) were treated with the PED. Thirty-four of 35 cases (97%) were successfully completed. A total of 64 PEDs were implanted, with the mean number of PEDs implanted per anterior and posterior circulation cases of 1.2 PEDs and 6.5 PEDs, respectively. A single PED was implanted in 73% of cases. Immediate flow disruption occurred in 97% of the cases. The overal rate of major stroke or mortality was 3% (1 of 35 patients). Minor stroke, cranial nerve palsy, transient neurological deficit, and groin complication occurred in one patient each (3% each, 12% total). Conclusion: Treatment of cerebral aneurysms with the PED carries an acceptable risk profile when a rigorous and uniform technique is used. Although the long-term results will need to be analyzed, the immediate procedural outcomes in our series using this technique appear quite promising. Competing interests: G Colby: None. L Lin: None. J Gomez: None. A Paul: None. J Huang: None. R Tamargo: None. A Coon: Covidien.